2021
DOI: 10.1155/2021/2475885
|View full text |Cite
|
Sign up to set email alerts
|

Application of Deep Learning in Financial Management Evaluation

Abstract: The competition among enterprises is becoming increasingly fierce. The research on the financial management evaluation model is helpful for enterprises to find possible risks as soon as possible. This paper constructs the financial management evaluation model based on the deep belief network and applies the analytic hierarchy process to determine the weight of financial management evaluation indicators, which is compared with other classical deep learning evaluation methods, such as KNN, SVM-RBF, and SVM linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…e core problem of the enterprise financial situation prediction model based on IDE-DBN is to determine the number of hidden node layers and the weight and bias between layers. e improved DE algorithm enhanced the global search performance and further reduced the local extremum [14].…”
Section: Prediction Modelmentioning
confidence: 99%
“…e core problem of the enterprise financial situation prediction model based on IDE-DBN is to determine the number of hidden node layers and the weight and bias between layers. e improved DE algorithm enhanced the global search performance and further reduced the local extremum [14].…”
Section: Prediction Modelmentioning
confidence: 99%
“…Testing [17] confirmed that the proposed system was feasible. Shi Wenlei constructed a financial management evaluation model based on a conviction network for predicting enterprise risk, which was verified to have a good predictive effect by hierarchical analysis method to strengthen the financial management, improve the capital market system, and promote the high-quality economic development of enterprises [18].…”
Section: Literature Reviewmentioning
confidence: 98%
“…Currently, financial management faces many challenges, such as inefficient data processing, financial reporting accuracy, cost control, and risk management [3]. Traditional financial management methods are inefficient in dealing with large-scale complex data, making it difficult to realize fast and accurate decision support [4]. Artificial intelligence technology, especially machine learning and data analysis, is increasingly used in financial management and can help companies automate the processing of large amounts of financial data, improving the efficiency and accuracy of data processing [5].…”
Section: Introductionmentioning
confidence: 99%